From within and in-between – co-designing organizational change. Issue 1 (2nd January 2021) - Salmi, Anna; Mattelmäki, Tuuli
ABSTRACT: This paper focuses on organizational change as a co-design challenge. Organizational change is addressed as a human process of relating that takes place in various interactions. This paper aims to contribute to a better understanding of what to consider when designers are facilitating co-design for organizational change. We draw from literature on both human-oriented organizational change and co-design. To illustrate how interactions take place in an organizational co-design project, we discuss accounts from a research project that aimed at improving collaborative innovation practices. We highlight that the meanings for change surfaced within organizations and in interaction. We bring to light the in-between space revolving around the two organizations: the facilitator team and the company project team. This temporary in-between space of co-design is facilitated by designers but filled in by participants' engagement and entangled interactions.